Pengaruh Bauran Pemasaran Jasa Pelayanan (Marketing Mix) Terhadap Loyalitas Pasien di Klinik Gigi Family Dental Care Daerah Bandung Wilayah Leuwipanjang, Buah Batu, Cibeureum dan Soreang - Ari Munandar; Kosasih Kosasih; Vip Paramarta; Farida Yuliaty; Rukhiyat Syahidin (Jurnal Ners, 2026)
This study aims to analyze the effect of the marketing mix of products, prices, promotions, places, people, processes, and physical evidence on patient loyalty at the Family Dental Care dental clinic in the Bandung area of Leuwipanjang, Buah Batu, Cibeureum, and Soreang. The marketing mix can be used as a marketing strategy to facilitate the clinic's or health service provider's marketing objectives. This study employs a survey method with a descriptive and verifiable approach. The sample used in this study consists of patients who visited the Family Dental Care dental clinic in the Bandung region, specifically in the areas of Leuwipanjang, Buah Batu, Cibeureum, and Soreang, with a total sample size of 384 respondents. The analysis used includes descriptive analysis and verifiable analysis using multiple linear regression. Result. The results of the descriptive analysis, when depicted using a continuum line, show that the marketing mix aspects of product, promotion, people, and physical evidence are rated as “Good to Very Good.” Meanwhile, the marketing mix aspect of place is rated as “Good.” The marketing mix aspects of price, process, and patient loyalty are rated as “Very Good,” which requires improvement and evaluation in order to address the shortcomings that have been identified. Meanwhile, the results of the confirmatory analysis using multiple linear regression analysis obtained from the regression equation are as follows: Y = -0.103 + 0.027X₁ + 0.364X₂ + 0.085X₃ + 0.375X₄ + 0.121X₅ – 0.097X₆ + 0.012X₇. The results of the multiple linear regression analysis indicate that the physical evidence variable contributes the least to patient loyalty compared to the other variables. In contrast, the process variable demonstrates that each increase in patients perception of the process factor leads to a decrease in patient loyalty by –0.097. Conclusion. The results of the hypothesis test using the t-test (paired) found that the product marketing mix and physical evidence variables did not have a significant effect on patient loyalty, while the price, promotion, place, and people marketing mix variables had a positive and significant effect on patient loyalty. Additionally, the process marketing mix variable had a negative and significant effect on patient loyalty. For the F test (simultaneous), the variables of product marketing mix, price, promotion, place, people, process, and physical evidence have a positive and significant effect on patient loyalty with a calculated F value > table F value (390.20 > 2.395).